Putative Role of Circulating Human Papillomavirus DNA in the Development of Primary Squamous Cell Carcinoma of the Middle Rectum: A Case Report - Ambrosio, Maria Raffaella; Vernillo, Remo; De Carolis, Sabrina; Carducci, Antonietta; Mundo, Lucia; Ginori, Alessandro; Rocca, Bruno Jim; Nardone, Valerio; Lucenti Fei, Alessandra; Carfagno, Tommaso; Lazzi, Stefano; Cricca, Monica; et al. (Frontiers in Oncology, 2019)
Here we present the case of a patient affected by rectal squamous cell carcinoma in which we demonstrated the presence of Human Papillomavirus (HPV) by a variety of techniques. Collectively, the virus was detected not only in the tumour but also in some regional lymph nodes and in non-neoplastic mucosa of the upper tract of large bowel. By contrast, it was not identifiable in its common sites of entry, namely oral, anal and uretral region. We also found HPV DNA in the plasma-derived exosome. Next, by in vitro studies, we confirmed the capability of HPV DNA-positive exosomes, isolated from the supernatant of a HPV DNA positive cell line (CaSki), to transfer its DNA to human colon cancer and normal cell lines. In the stroma nearby the tumor mass we were able to demonstrate the presence of virus DNA in the stromal compartment, supporting its potential to be transferred from epithelial cells to the stromal ones. Thus, this case report favours the notion that human papillomavirus DNA can be vehiculated by exosomes in the blood of neoplastic patients and that it can be transferred, at least in vitro, to normal and neoplastic cells. Furthermore, we showed the presence of viral DNA and RNA in pluripotent stem cells of non-tumour tissue, suggesting that after viral integration (as demonstrated by p16 and RNA in situ hybridization positivity), stem cells might have been activated into cancer stem cells inducing neoplastic transformation of normal tissue through the inactivation of p53, p21 and Rb. It is conceivable that the virus has elicited its oncogenic effect in this specific site and not elsewhere, despite its wide anatomical distribution in the patient, for a local condition of immune suppression, as demonstrated by the increase of T-regulatory (CD4/CD25/FOXP3 positive) and T-exhausted (CD8/PD-1 positive) lymphocytes and the M2 polarization (high CD163/CD68 ratio) of macrophages in the neoplastic microenvironment. It is noteworthy that our findings depicted a static picture of a long-lasting dynamic process that might evolve in the development of tumors in other anatomical sites.